Prognostic Significance of Lymphocyte-to-Monocyte and Platelet-to-Lymphocyte Ratio in Rectal Cancer: A Systematic Review, Meta-analysis, and Meta-regression. Issue 2 (February 2022) - Hamid, Hytham K.S.; Emile, Sameh H.; Davis, George N.
Abstract : BACKGROUND: The low lymphocyte-to-monocyte ratio and high platelet-to-lymphocyte ratio have been reported to be poor prognostic indicators in various solid tumors, but the prognostic significance in rectal cancer remains controversial. OBJECTIVES: We sought to determine the prognostic value of the lymphocyte-to-monocyte ratio and the platelet-to-lymphocyte ratio following curative-intent surgery for rectal cancer. DATA SOURCES: Following PRISMA guidelines (PROSPERO, ID: CRD42020190880), PubMed and Embase databases were searched through January 2021 including 3 other registered medical databases. STUDY SELECTION: Studies evaluating the impact of pretreatment lymphocyte-to-monocyte ratio and platelet-to-lymphocyte ratio on overall or disease-free survival in patients undergoing curative rectal cancer resection were selected. MAIN OUTCOMES MEASURES: The main outcome measures were overall and disease-free survival. RESULTS: A total of 23 studies (6683 patients) were included; lymphocyte-to-monocyte ratio and platelet-to-lymphocyte ratio were evaluated in 14 and 16 studies. A low lymphocyte-to-monocyte ratio was associated with poorer overall survival (HR, 1.57; 95% CI, 1.29–1.90; p < 0.001) and disease-free survival (HR, 1.29; 95% CI, 1.13–1.46; p < 0.001). However, when the analysis was limited to patients treated with surgery alone or to those with stage I to III tumors, lymphocyte-to-monocyte ratio was not a predictor of overall survival and disease-free survival. The platelet-to-lymphocyte ratio did not predict for overall or disease-free survival, regardless of the treatment modality, studied population, tumor stage, or cutoff value. Finally, a low lymphocyte-to-monocyte ratio, but not a high platelet-to-lymphocyte ratio, was inversely correlated with complete pathologic response rate. LIMITATIONS: The retrospective nature of most included studies was a limitation. CONCLUSIONS: Pretreatment lymphocyte-to-monocyte ratio, but not platelet-to-lymphocyte ratio, correlates with tumor response to neoadjuvant chemoradiotherapy and poorer prognosis after curative-intent surgery for rectal cancer, and it potentially represents a simple and reliable biomarker that could help optimize individualized clinical decision-making in high-risk patients. REGISTRATION: https://www.crd.york.ac.uk/prospero/ ; ID: CRD42020190880 Abstract : Supplemental Digital Content is available in the text.